Inmigración, inserción y distribución de los montañeses en las regiones del sur peruano en la era borbónica - Sánchez-Concha Barrios, Rafael (2025)
This research explains and analyzes the «montañeses» (or Cantabrian) presence in Peru during the Bourbon era, specifically its distribution in the diocesan areas of the southern viceroyalty: Arequipa, Huamanga, and Cuzco. This historical phenomenon is studied by highlighting the most significant cases of the mentioned Spanish group, through their leading role and their ties to the social elites of southern Peru in the late viceregal period.